Fungi in salterns - Chung, Dawoon; Kim, Haryun; Choi, Hyun Seok (The journal of microbiology, 2019)
Salterns are hypersaline extreme environments with unique physicochemical properties such as a salinity gradient. Although the investigation of microbiota in salterns has focused on archaea and bacteria, diverse fungi also thrive in the brine and soil of salterns. Fungi isolated from salterns are represented by black yeasts ( Hortaea werneckii , Phaeotheca triangularis , Aureobasidium pullulans , and Trimmatostroma salinum ), Cladosporium , Aspergillus , and Penicillium species. Most studies on saltern-derived fungi gave attention to black yeasts and their physiological characteristics, including growth under various culture conditions. Since then, biochemical and molecular tools have been employed to explore adaptation of these fungi to salt stress. Genome databases of several fungi in salterns are now publicly available and being used to elucidate salt tolerance mechanisms and discover the target genes for agricultural and industrial applications. Notably, the number of enzymes and novel metabolites known to be produced by diverse saltern-derived fungi has increased significantly. Therefore, fungi in salterns are not only interesting and important subjects to study fungal biodiversity and adaptive mechanisms in extreme environments, but also valuable bioresources with potential for biotechnological applications.